Influence of some reaction parameters on the synthesis of the first generation of stars with arms composed of poly(oxyethylene glycol) - Łapienis, G. (Polimery, 2022)
The syntheses of the multiarm stars resulting from the reaction of oligoalcohols with diepoxides have been studied. MPEG 550, 750, and 2000 [MPEG=monomethyl ether of poly(oxyethylene glycol)] as precursors of arms and diglycidyl ethers of ethylene (DGEG) or neopentyl glycol (DGNG) as the core forming diepoxides were used. The increase in Mn, polydispersity (MWD) and the number of arms (f) in stars with the increase in the concentration of reagents and [diepoxide]o/ [MPEG]o ratio, and the decrease in temperature were observed. The final content of unreacted MPEG lowers with increasing concentration of reagents, proportion of the alkoxide groups in the initiator ([RO-]/[RO-+ROH]), length of MPEG chain, and [diepoxide]o/[MPEG]o ratio and also with decreasing reaction temperature.